Sodium houttuyfonate affects production of N-acyl homoserine lactone and quorum sensing-regulated genes expression in Pseudomonas aeruginosa - Wu, Daqiang; Huang, Weifeng; Duan, Qiangjun; Li, Fang; Cheng, Huijuan (Frontiers in Microbiology, 2014)
Quorum sensing (QS) is a means of cell-to-cell communication that uses diffusible signaling molecules that are sensed by the population to determine population density, thus allowing co-ordinate gene regulation in response to population density. In Pseudomonas aeruginosa, production of the QS signaling molecule, N-acyl homoserine lactone (AHL), co-ordinates expression of key factors of pathogenesis, including biofilm formation and toxin secretion. It is predicted that the inhibition of AHL sensing would provide an effective clinical treatment to reduce the expression of virulence factors and increase the effectiveness of antimicrobial agents. We previously demonstrated that sodium houttuyfonate (SH), commonly used in traditional Chinese medicine to treat infectious diseases, can effectively inhibit QS-regulated processes, including biofilm formation. Here, using a model system, we demonstrate that SH causes the dose-dependent inhibition of AHL production, through down-regulation of the AHL biosynthesis gene, lasI. Addition of SH also resulted in down-regulation of expression of the AHL sensor and transcriptional regulator, LasR, and inhibited the production of the QS-regulated virulence factors, pyocyanin and LasA. These results suggest that the antimicrobial activity of SH may be due to its ability to disrupt QS in P. aeruginosa.